1979
DOI: 10.1073/pnas.76.4.1828
|View full text |Cite
|
Sign up to set email alerts
|

Solubilized and insolubilized bone morphogenetic protein.

Abstract: A bone morphogenetic protein (BMP) obtained in solution by digestion of demineralized rabbit cortical bone matrix with bacterial coliagenase retains its biologically active conformation in a neutral salt/ethylene glycol mixture. BMP may be insolubilized by coprecipitation with calcium phosphate and resolubilized by chemical extraction with a neutral salt in the same solvent mixture. Upon concanavalin A-Sepharose chromatography, BMP is boundby hydrophobic interaction and carbohydrate recognition and is recovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
205
0
6

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 432 publications
(214 citation statements)
references
References 25 publications
3
205
0
6
Order By: Relevance
“…Urist believed that osteoinduction by demineralised bone [72], was caused by a contained factor which he named bone morphogenetic protein (BMP), and in 1979 the group isolated an extract of osteoinductive glycoproteins [73]. In 1988, Wozney et al extracted 40 µg inductive proteins from 40 kg of bone.…”
Section: Bmpsmentioning
confidence: 99%
“…Urist believed that osteoinduction by demineralised bone [72], was caused by a contained factor which he named bone morphogenetic protein (BMP), and in 1979 the group isolated an extract of osteoinductive glycoproteins [73]. In 1988, Wozney et al extracted 40 µg inductive proteins from 40 kg of bone.…”
Section: Bmpsmentioning
confidence: 99%
“…Several osteoinductive growth factors, referred to as the bone morphogenetic proteins (BMP), have been shown to induce the transformation of undifferentiated mesenchymal cells into chondroblasts and osteoblasts, resulting in the formation of de novo bone [2, 18, 19, 22, 36, 42, 43, 47, 55,72,73]. Numerous preclinical animal studies have demonstrated the superiority of BMP implants over traditional autogenous bone grafts for a variety of orthopedic applications [17, 25, 29, 32, 37, 49,66].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies on the development of new implantable biomaterials as bone substitutes in the reparation of bone defect, BMP bound to 3-TCP, HAP and human fibrin have been investigated (Urist et al 1979, Kawamura et al 1988, Mieki 1990). Mieki (1990) reported that the osteoinductive activity of HAP/BMP complex was higher than that of BMP alone.…”
Section: Discussionmentioning
confidence: 99%